ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK PADA KANTOR DESA MEKAR SEKUNTUM KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Indrayani, Indrayani; Haryono, Haryono (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
The village is the smallest government administration device in society. The village becomes a unit in service to the village community through village officials, the service unit is one of the main indicators of the success of the village community, the community satisfaction indicator is the main indicator in producing quality and quality services. The purpose of this study was to find out how satisfied the people of Mekar Sekuntum Village, Teluk Keramat District, Sambas Regency, were in responding to village office services during the service process to the community. Data collection was carried out using the questionnaire method while data analysis used the community satisfaction index (IKM). The research sample is the community of the village of Mekar Sekuntum, Teluk Keramat sub-district, Sambas district, totaling 17 people. The results of this study indicate that the overall score of 69.75 from the indicators tested indicates that the services of the Mekar Sekuntum village office can be said to be GOOD because they are in category B.